ON THE SPECTRUM OF SPECIAL CLASSES OF DOUBLY COMMUTING n −TUPLES OF OPERATORS - Ahmed, Buthainah; Al-Janaby, Hiba (Iraqi Journal of Science, 2024)
In this paper we study a spectral characterization of the Taylor-Browder spectrum fora double commuting n − tuple of totally θ −operators, and study relation between theTaylor- Weyl spectrum, Taylar- Browder spectrum, joint-Weyl spectrum, and joint-Browder spectrum for commuting n − tuple of totally θ −operators. Also we study aspectral characterization of the Taylor-Browder spectrum for a doubly commutingn − tuple of posinormal operators.